Study on the Pharmacokinetic Profiles of Three Ingredients in Qilong Capsules and Their Potential Interactions in Rats by LC–MS/MS. (31st May 2021) - Liu, Ruichen; Liang, Huiliang; Li, Zhen; Zang, Hengchang
Abstract: : Qilong capsule (QLC) is a well-known Traditional Chinese Medicine, and it has a long history for the treatment of ischemic stroke. Its major ingredients are saponins, such as paeoniflorin, amygdalin and calycosin-7-glucoside, contributing to vasodilation function. In this study, a simple, rapid and sensitive high-performance liquid chromatography-tandem mass spectrometry method was developed to determine three bioactive ingredients in rat plasma after oral administration of QLC. A simple acetonitrile precipitation method was introduced during the sample preparation. Chromatographic separation was performed on a Shiseido CAPCELL PAC MGIII-C18 column using a gradient elution with acetonitrile and water (0.1% formic acid) as a mobile phase, and the chromatographic separation was 5 min. The methodological evaluation showed that this method had a high sensitivity (the lower limit of quantification was 1 ng/mL for calycosin-7-glucoside, 5 ng/mL for paeoniflorin, 5 ng/mL for amygdalin), satisfactory accuracy (relative error ≤ ±15%) and precision (relative standard deviation ≤15%). Then, the analytical method was applied to the pharmacokinetic study in rats following oral administration of the extracts in QLC. Meanwhile, the pharmacokinetic parameters of complex system in QLC were analyzed and the potential interaction between ingredients was explored. The present quantification method and pharmacokinetic study will provide a meaningful reference for the formulas research of QLC in the treatment of ischemic stroke. Highlight: A simple, rapid and sensitive HPLC–MS/MS analytical method was developed for the simultaneous determination of three ingredients in rat plasma after oral administration of QLC. A simple acetonitrile precipitation method was introduced to extract three biomedical ingredients during the plasma sample preparation. The pharmacokinetic results revealed the pharmacological active substances, identified internal variation rules and provided a meaningful reference for the formulas research of QLC in the treatment of ischemic stroke.